Pollution removal from leachate using bottom ash-bentonite-zeolite liner - Mollamahmutoglu, Ayse Sandikci; Kanat, Gurdal; Turkdogan, F. Ilter (ELSEVIER SCIENCE INC, 2019)
There is a crucial need for the development of a landfill liner that can effectively prevent the transport of contaminants in solid waste landfills. The search for strongly adsorbing materials with high treatment efficiency is still continuing. In this study, removal of organics (COD, total-P and TKN parameters) and heavy metals were investigated in the form of a liner formed by mixing the bottom ash and zeolite with bentonite. The various mixture ratios were prepared and studied in order to provide optimum value of impermeability coefficient and heavy metal/organic pollution retention efficiency. The lowest permeability was found to be provided by 30% ratio in bentonite. The overall rate of heavy metal removal from the leachate was up to 98%, while COD, TSS, total-P and TKN were removed in the rates of 98, 85-97, 83-96 and 96-98% respectively. Higher efficiency was found particularly for Zn, Pb and Ni removal. In the study, moreover, cost evaluation was also made for the materials.
Keywords: Bottom ash; Bentonite; Zeolite; Heavy metal removal; Leachate; MSW LANDFILL LEACHATE; COAL; Engineering; Water Resources